Analisis Pola Makanan Tambahan Sebagai Faktor Risiko Stunting Pada Balita di Puskesmas Pasar Prabumulih - Herza Olivina; Munaya Fauziah; Tria Astika Endah Permatasari; Andriyani Andriyani; Dewi Purnamawati (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
This study aims to elaborate on the pattern of additional food as a risk factor for stunting in toddlers at the Pasar Prabumulih Health Center in 2023. Stunting is a condition where a child's height is shorter than the height of other children of the same age. Factors that can influence stunting include unhealthy eating patterns, low birth weight (LBW), lack of breastfeeding, due to infectious diseases during infancy, and failure to achieve perfect growth improvement in the following period. This study uses a case-control study approach with an analytical observational research design. Cases are toddlers diagnosed with stunting and controls are toddlers diagnosed as normal. The data collection technique uses primary data obtained directly from the research site by means of observation and interviews using questionnaires. Data were analyzed using binary logistic regression tests. The results of the analysis showed that there was no relationship between exclusive breastfeeding, parental education level, parental knowledge, and history of infectious diseases with stunting, but additional food patterns were related to stunting. The final multivariate model showed that only additional food patterns affected stunting.